Human parasitology - Bogitsh, Burton J. (Burton Jerome); Carter, Clint E. (Clint Earl); Oeltmann, Thomas N. (Academic Press, an imprint of Elsevier, 2019)
This edition emphasizes a medical perspective while incorporating functional morphology, physiology, biochemistry, and immunology to enhance appreciation of the diverse implications of parasitism. Bridging the gap between classical clinical parasitology texts and traditional encyclopedic treatises. This book appeals to students interested in the medical aspects of parasitology and those who require a solid foundation in the biology of parasites. This 5th edition has been fully revised to integrate the most recent molecular discoveries regarding host-parasite relationships as well as the most effective therapeutic regimens. --